Analisis Eksistensi Benda Cagar Budaya Dalam Tata Ruang Kota Guna Mendukung Pelestariannya di Kota Surakarta. - Nindya Ayu Wardani; Baba Barus; Siti Nurisyah (Diponegoro University, 2020)
The City of Surakarta, one of National Activity Center and also known as Eco Cultural City, has 171 cultural heritage objects have to be preserved. City development that leads to modernization, physically, is a threat to the existence of those cultural heritage objects.To minimize lost of these valuable objects, risk management method, which is based on the interaction between their vulnerability and hazard, could be carried out. This study was aimed to identify and categorize cultural heritage objects at the city, to analyze the risk of losing of cultural heritage objects, and to recommend future city spatial planning in relation to cultural heritage objects. This research was conducted through visual classification techniques on high resolution satellite imagery, Weighted Overlay, Overlay Analysis and Descriptive Analysis. Surakarta City's cultural heritage objects mostly have 100-200 years old which is dominated by traditional Javanese architectural styles. Cultural heritage objects are not fully in good condition, as many as 35 units were partially damaged, 9 units suffered total damage, and 5 units have experienced modernization. A total of 33 cultural heritage objects covered an area of 886,556 square meters (46.09%) are at a high risk of losing their existence. To protect the existence of cultural heritage, the result research should to considered of the city developtment program.